Macroalgae Extracts From Antarctica Have Antimicrobial and Anticancer Potential - Martins, Rosiane M.; Nedel, Fernanda; Guimaraes, Victoria B. S.; Silva, Adriana F. da; Colepicolo, Pio [UNESP]; Pereira, Claudio M. P. de; Lund, Rafael G. (Frontiers Media Sa, 2018)
Background: Macroalgae are sources of bioactive compounds due to the large number of secondary metabolites they synthesize. The Antarctica region is characterized by extreme weather conditions and abundant aggregations of macroalgae. However, current knowledge on their biodiversity and their potential for bio-prospecting is still fledging. This study evaluates the antimicrobial and cytotoxic activity of different extracts of four macroalgae (Cystosphaera jacquinotii, Iridaea cordata, Himantothallus grandifolius, and Pyropia endiviifolia) from the Antarctic region against cancer and non-cancer cell lines. Methods: The antimicrobial activity of macroalgae was evaluated by the broth microdilution method. Extracts were assessed against Staphylococcus aureus ATCC 19095, Enterococcus faecalis ATCC 4083, Escherichia coli ATCC29214, Pseudomonas aeruginosa ATCC 9027, Candida albicans ATCC 62342, and the clinical isolates from the human oral cavity, namely, C. albicans (3), C. parapsilosis, C. glabrata, C. lipolytica, and C. famata. Cytotoxicity against human epidermoid carcinoma (A-431) and mouse embryonic fibroblast (NIH/3T3) cell lines was evaluated with MTT colorimetric assay. Results: An ethyl acetate extract of H. grandifolius showed noticeable antifungal activity against all fungal strains tested, including fluconazole-resistant samples. Cytotoxicity investigation with a cancer cell line revealed that the ethyl acetate extract of I. cordata was highly cytotoxic against A-431 cancer cell line, increasing the inhibitory ratio to 91.1 and 95.6% after 24 and 48 h exposure, respectively, for a concentration of 500 mu g mL(-1). Most of the algal extracts tested showed little or no cytotoxicity against fibroblasts. Conclusion: Data suggest that macroalgae extracts from Antarctica may represent a source of therapeutic agents. HIGHLIGHTS Different macroalgae samples from Antarctica were collected and the lyophilized biomass of each macroalgae was extracted sequentially with different solvents The antimicrobial and anticancer potential of macroalgae extracts were evaluated Ethyl acetate extract of H. grandifolius showed noticeable antifungal activity against all the fungal strains tested, including fluconazole-resistant samples Ethyl acetate extract of I. cordata was highly cytotoxic against the A-431 cancer cell line Most of the algal extracts tested showed little or no cytotoxicity against normal cell lines
Keywords: marine natural products; seaweeds; antibacterial agents; antifungal agents; antineoplastic agents